“Primitive” and “naïve” in the exhibition Lirismo Brasileiro / 68 - Lima, Gabriela Kalindi Daduch; Oliveira, Emerson Dionisio Gomes de (Farol, 2024)
The classifications “naïve” and “primitive” in the artistic circuit of the 1960s in Brazil were, among others, linked to productions aimed at the popular. The article analyzes these classifications in the discourses undertaken in the exhibition Lirismo Brasileiro / 68, held in 1968, in Lisbon. To this end, it reflects on what the Itamaraty, when organizing the exhibition, called Brazilian lyricism and what idea of ​​Brazil was presented, in the context of a dictatorial period.